Polarographic/voltammetric behaviour of colloidal solutions. A brief review - Heyrovský, Michael (Univerzita Pardubice, 1997)
Ultrasmall SnO2, TiO2 and mixed Fe2O3 + TiO2 colloids in acidic solutions yield diffusion-controlled cathodic currents at polarized mercury electrodes, due to electroreduction of protons localized at the surface of the particles. The primarily generated hydrogen atoms reduce then the material of the particles chemically. Besides that as a parallel electrode reaction a direct reduction by electrons of Sn(IV), Ti(IV) and Fe(III), respectively, takes place.